2018
DOI: 10.3390/min8110505
|View full text |Cite
|
Sign up to set email alerts
|

Plant Tissues and Embryos Biominerals in Sarcocornia pruinosa, a Halophyte from the Río Tinto Salt Marshes

Abstract: Although biomineralization in plants is an important area of research, there is very limited information. In this work, we report the location of Na, K, Ca, Mg and Fe biominerals in Sarcocornia pruinosa (Chenopodiacaeae), a halophyte species growing in the estuarine area of Río Tinto, an extreme acidic environment. The estuarine soils of the Tinto basin are characterized by slightly acidic pH and high concentrations of ions. They are exposed to Atlantic Ocean tides that contribute to the increase in pH, Na and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…The Chenopodiaceae species are generally characterized by a high content of minerals, polyphenols, and fatty acids, among other compounds of interest. The abundance of inorganic elements (Na + , K + , Mg 2+ , and Ca 2+ , among others) in the tissues of these plants, together with the wide diversity of bioactive compounds, have been related to their capacity to survive and grow in extreme environments with high salinity and long periods of intense drought [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Chenopodiaceae species are generally characterized by a high content of minerals, polyphenols, and fatty acids, among other compounds of interest. The abundance of inorganic elements (Na + , K + , Mg 2+ , and Ca 2+ , among others) in the tissues of these plants, together with the wide diversity of bioactive compounds, have been related to their capacity to survive and grow in extreme environments with high salinity and long periods of intense drought [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in this study confirm many of the adaptive strategies reported in the literature for dicotyledonous succulent halophytes. The anatomy of the stem sections was like other articulated succulent species, with the presence of a special water storage tissue that included big cells with large vacuoles filled with salt (Grigore et al 2011;Fuente et al 2018). Additionally, the quantitative abundance of the elements analyzed matched the general pattern described for halophytes (Chaudhary 2019), with Na being the main element in the total concentration, followed by Mg, K and Ca.…”
Section: Discussionmentioning
confidence: 67%
“…Other biominerals reported in plants are magnesium oxalates, silica, and iron in the form of jarosite and Fe-oxides (Monje and Baran 2005;Rodríguez et al 2005). Fuente et al (2018) have identified the chlorides halite and sylvite, and the oxalates glushinskite and weddellite in the succulent stem tissue of the littoral halophyte Sarcocornia pruinosa. However, there is a lack of information about the existence of seasonal changes in this process and the effect of soil composition on the biomineral composition of plants that adapt to salinity in the same way.…”
Section: Introductionmentioning
confidence: 99%
“…The main effect revealed by in-situ measurements is the plumbojarosite and whewellite disappearance. The latter is one of the most common phases in plants tissues, commonly occurring within the cells but also in extracellular form [79,80]. Whewellite is stable up to 400 °C as already reported by Quintana et al [81] and above this temperature it decomposes, probably forming calcite [82,83].…”
Section: Discussionmentioning
confidence: 79%